Advanced vat photopolymerization of polymer-derived 70S30C glass-carbon nano-composites: Topological control and biological validation - Elsayed, Hamada (2025)
This study explores the use of photocurable silicone/acrylate blends as feedstock for vat-photopolymerization to fabricate highly porous components with complex geometries, such as gyroid scaffolds. The inclusion of calcium nitrate tetrahydrate in nano-emulsion into the silicone-based liquid enables the transformation of polymer scaffolds into ceramic nanocomposites by heat treatment at 700 ◦C in a N2 atmosphere. These scaffolds are designed for bioengineering applications, featuring a matrix resembling 70S30C bioglass with pyrolytic carbon as a secondary phase. The homogeneity of the feedstock, essential for developing a glass matrix, does not automatically ensure tight control over topology and mechanical properties. However, by utilizing high-precision stereolithography and liquid feedstock-based emulsion inks, we achieved a strict match to the reference model porosity (85 vol%) for both printed and fired scaffolds, resulting in an impressive strength-to-density ratio. In vitro tests with multiple human cell lines confirm the biocompatibility and bioactivity of our materials. Furthermore, the enhanced photothermal effect attributable to increased infrared absorption of the dispersed carbon phase enhanced by infrared absorption, shows promising potential for inducing apoptosis in cancer cells, providing an exciting avenue for cancer treatment applications.